TINGKAT KESUKAAN BUBUK DAUN KELOR UNTUK FORMULA MAKANAN BALITA STUNTING - Julians A.S. Letiora; Jufri Sineke; Rudolf Boyke Purba (Jurnal GIZIDO, 2020)
Stunting is a major public health problem in low and middle income countries. Overcoming malnourished toddlers. Can be done by providing energy and protein-dense formulas. Consumption of Moringa leaves is an alternative to overcome cases of malnutrition in Indonesia. This type of experimental research uses organoleptic test research design to measure the preference level of stunting toddler food formulas. The results of the test of the level of preference for the color, taste, texture and aroma of Moringa porridge were carried out three times in the test, there were many who chose to like the 30.0% color test, in the taste test many chose to like it a little (45.0%), for the texture test many chose like 40.0% and for the aroma test, many people prefer to like it (32.5%). Conclusion: Moringa porridge has an influence on physical characteristics, organoleptic hedonic color, taste, texture and aroma. The more moringa powder used, the lower the color brightness of the moringa pulp and also the texture. The higher the addition of Moringa leaf powder will have an effect on the increase in aroma and bitter taste.